Variability and Individual Differences in Early Social Perception and Social Cognition - Alia Martin (Frontiers Research Topics, 2016)
Over the past three decades mounting evidence has suggested that infants' social perceptual and social cognitive abilities are considerably richer than was once thought. By the end of the second year of life, infants discriminate faces along various social dimensions, attend to and understand others' goals and intentions, use the emotions of others to guide their learning and behavior, attribute dispositional characteristics to other agents, and make basic social evaluations. What has also become clear is that there is a great deal of variability in infants' social perception and cognition. A critical, outstanding question concerns the nature and meaning of such variability. The proposed Research Topic welcomes papers addressing cutting-edge questions regarding variability and individual differences in early social perception and social cognition. The goal of these papers is to investigate overarching questions in this domain, which are necessary to move the field forward. Variability in early social perception and social cognition (among other domains) in infancy and early childhood is often attributed to noise, or overlooked in favor of focusing on age-related changes. Yet, recent work suggests that variability in social perceptual and social cognitive tasks reliably inter-relates, and predicts real-world social behaviors. For example, infants' everyday experience with different face categories predicts individual differences in face processing, infants' production of goal-directed actions predicts their simultaneous understanding of these actions, and variability in social attention during the second year of life is related to theory of mind during the preschool years. These findings suggest that variability in performance on social perception and social cognition tasks is not merely a nuisance variable, but, rather, may provide the key to addressing significant questions regarding the nature of infants' social perception and social cognition, and the processes that underlie developmental change. Acknowledging and closely examining and investigating variability in early social perceptual and social cognitive abilities may represent a powerful approach for understanding development in (at least) two ways. First, variability can signal transitional points in the developmental onset of a given ability. Thus, such variability, and the extent to which variability relates to experience and/or other abilities, can be used to test hypotheses regarding mechanisms that underlie developmental changes. Second, variability can represent more enduring individual differences between infants. In this case, critical questions arise regarding the source of individual differences (that is, what factors shape the emergence of individual differences?) and whether such early individual differences contribute to the development of more advanced and sophisticated forms of social cognition and behavior. The goal of this Research Topic will be to encourage researchers to take variability in early social perception and cognition seriously. Papers that give variability center stage, and are aimed at addressing the value of variability for identifying developmental mechanisms, as well as investigating the existence, source, and antecedents of early individual differences in social perception and social cognition are welcomed. Taken together, the contributed papers will provide integral new information to the study of social perception and social cognition over the first three years of life.